Autophagy Proteins in Phagocyte Endocytosis and Exocytosis - Münz, Christian (Frontiers in Immunology, 2017)
Autophagy was initially described as a catabolic pathway that recycles nutrients of cytoplasmic constituents after lysosomal degradation during starvation. Since the immune system monitors degradation products for lysosomal degradation via major histocompatibility complex (MHC) class II restricted antigen presentation, autophagy was found to process intracellular antigens for display on MHC class II molecules. In recent years, however, it has become apparent that the molecular machinery of autophagy serves phagocytes in many more membrane trafficking pathways, thereby regulating immunity to infectious disease agents. In this minireview we will summarize the recent evidence that autophagy proteins regulate phagocyte endo- and exocytosis for myeloid cell activation, pathogen replication and MHC class I and II restricted antigen presentation. Selective stimulation and inhibition of the respective functional modules of the autophagy machinery might constitute valid therapeutic options in the discussed disease settings.